The Effect of Friction Stir Welding Parameters on the Weldability of Aluminum Alloys with Similar and Dissimilar Metals: Review - Khalafe W.H.; Sheng E.L.; Bin Isa M.R.; Omran A.B.; Shamsudin S.B. (MDPI, 2023)
The solid-state welding method known as friction stir welding (FSW) bonds two metallic work parts, whether the same or different, by plastically deforming the base metal. The frictional resistance between both metallic workpieces causes them to produce heat, which produces plastic deformation and welds them. However, the weldability and strength of FSW joints mainly depend on the FSW parameters. This review work highlights the previous research work on the FSW parameters and their effects on the weldability and quality of the aluminum alloys joined with similar and dissimilar metals through the FSW method. About 150 research studies were systematically reviewed, and the articles included data from peer-reviewed journals. It has been concluded that the key parameters, including welding speed, rotational speed, plunge depth, spindle torque, shoulder design, base material, pin profile and tool type, significantly affect the weldability of the aluminum joint through the FSW method. Also, the selection of these parameters is important and fundamental as they directly affect the joint. It is recommended that future work focuses on FSW for aluminum. Among these, the most essential is the application of artificial intelligence (AI) techniques to select the optimum FSW parameters for aluminum welding. 2022 by the authors.